Predictive Factors of Lymph Node Metastasis in Patients With Papillary Microcarcinoma of the Thyroid: Retrospective Analysis on 293 Cases - Medas, Fabio; Canu, Gian Luigi; Cappellacci, Federico; Boi, Francesco; Lai, Maria Letizia; Erdas, Enrico; Calò, Pietro Giorgio (Frontiers in Endocrinology, 2020)
Introduction: Papillary thyroid microcarcinoma (PTMC) is defined as a tumor with a larger diameter ≤ 1 cm and is considered having an indolent course and an excellent prognosis. Nevertheless, the incidence of lymph node metastasis in PTMC is not negligible, reaching up to 65% in some series. The aim of this study was to assess the incidence of lymph node metastasis in patients with PTMC and to evaluate predictive factors for lymph node metastasis. Methods: We included in this retrospective observational study patients who underwent thyroidectomy with pathological diagnosis of PTMC at our department from January 2003 to June 2019. Results: Two hundred ninety-three patients were included in the study. The incidence of lymph node metastasis was 13.7%. Multivariate analysis revealed as independent risk factors for lymph node metastasis age <45 years, nodule size ≥6 mm, tall cell variant of PTC, extrathyroidal extension, and angioinvasion. Conversely, autoimmune thyroiditis was found as a protective factor for lymph node metastasis. A subgroup of patients, with nodule size ≤ 5 mm, presented non-aggressive features. Conclusion: The incidence of lymph node metastasis in PTMC is considerable; the size of the tumor appears to be the most significant predictive factor for lymph node metastasis. The traditional cut-off value used for definition of microcarcinoma could be reconsidered to identify patients with an indolent course of the tumor, where active surveillance could be the appropriate treatment, and on the other hand, patients with potentially aggressive tumors requiring an adequate surgical intervention. Clinical Trial Registration: The trial was registered at ClinicalTrials.gov (ID: NCT04274829).